The sociodynamics of chemsex: Stakeholders’ perspectives in France - Results from the ANRS-PaacX study - Nicolas Khatmi; Perrine Roux; Bruno Spire; Christel Protière (SSM: Qualitative Research in Health)
This study examined the intricate phenomenon of chemsex among men who have sex with men (MSM) in France, by focusing on the perspectives of different stakeholders, namely people with chemsex experience, clinicians, and community health workers. Employing a sociodynamic approach, lexical analysis was used to identify and interpret key themes in participants’ discourses on chemsex, with a view to revealing its multifaceted nature.Our findings highlight how the social representations of chemsex are profoundly influenced by the institutional separation of sexual healthcare services from services managing the consumption of psychoactive substances. This division not only shapes how individuals perceive and manage their behaviors and health needs but also introduces systemic challenges to adequately addressing the health issues of MSM engaged in chemsex. Moreover, this division leads to structural obstacles for clinicians and community health workers providing care.This comprehensive analysis deepens our understanding of the complex mechanisms underlying chemsex and offers essential insights for crafting informed and effective public health interventions. Furthermore, our study results underscore the critical need for community involvement in strategies focused on addressing the unique health and social challenges posed by chemsex. Moreover, our findings advocate integrated approaches that align with the specific needs and experiences of concerned stakeholders.